2017
DOI: 10.1177/1754073916684558
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Core of Emotion: Linking Pleasure, Subjective Well-Being, and Optimal Metastability in the Brain

Abstract: Arguably, emotion is always valenced—either pleasant or unpleasant—and dependent on the pleasure system. This system serves adaptive evolutionary functions; relying on separable wanting, liking, and learning neural mechanisms mediated by mesocorticolimbic networks driving pleasure cycles with appetitive, consummatory, and satiation phases. Liking is generated in a small set of discrete hedonic hotspots and coldspots, while wanting is linked to dopamine and to larger distributed brain networks. Breakdown of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 89 publications
1
83
1
Order By: Relevance
“…What has emerged from the cross-sectional studies of the parental brain is the engagement of brain networks known to play roles in emotion, pleasure, social interactions, mentalization, and embodied simulation [57, 62, 63]. Important hubs in these emotional networks include the orbitofrontal cortex, anterior cingulate cortex, anterior insula, amygdala, and supplementary motor area [64].…”
Section: Facilitation Of Parental Capacities For Caregivingmentioning
confidence: 99%
“…What has emerged from the cross-sectional studies of the parental brain is the engagement of brain networks known to play roles in emotion, pleasure, social interactions, mentalization, and embodied simulation [57, 62, 63]. Important hubs in these emotional networks include the orbitofrontal cortex, anterior cingulate cortex, anterior insula, amygdala, and supplementary motor area [64].…”
Section: Facilitation Of Parental Capacities For Caregivingmentioning
confidence: 99%
“…Therefore, disillusionment could be linked to signs that a partner may not provide needed resources for the raising of offspring or even signs that the partner may present a danger to physical safety. Because the literature documents instances of the same brain area being linked to both strong positive and strong negative emotions, the amygdala (Aamodt & Wang, 2008) and insula (Chua et al, 2009;Kringelbach & Berridge, 2017) have been linked to positive marital states (Acevedo et al, 2012a(Acevedo et al, , 2012b and may also pertain to the negative romantic relationship states we are investigating in our study.…”
Section: Amygdalamentioning
confidence: 95%
“…Brain networks related to mind-wandering and mindfulness, have also been found to be involved in subjective well-being, further corroborating the present results. Kringelbach and Berridge (2017) demonstrated that the pleasure system is included in the default mode network. This suggests that brain areas related to self-processing are also related to subjective well-being, which is consistent with our finding of the moderated positive relations between daydreaming and subjective well-being.…”
Section: Theoretical Significancementioning
confidence: 99%